UJI EFEKTIVITAS PUPUK ORGANONITROFOS DAN KOMBINASINYA DENGAN PUPUK KIMIA TERHADAP PERTUMBUHAN, SERAPAN HARA DAN PRODUKSI TANAMAN JAGUNG MANIS (ZEA MAYS SACCHARATA ) DI MUSIM TANAM KETIGA PADA TANAH ULTISOL GEDUNG MENENG - Sari, Eka Purnama; Lumbanraja, Jamalam; Buchari, Henrie; Niswati, Ainin (Politeknik Negeri Lampung., 2015)
Organonitrofos fertilizer is organic fertilizer derived from cow manure enriched with rock phosphate and microbial activity involves fastening N and phosphate newly developed solvent. This study aimed to determine dose combination Organonitrofos fertilizers and inorganic fertilizers are most effective against the growth, nutrient uptake, and yield of sweet corn. This research was conducted in November 2012 until March 2013 in the Integrated Field Laboratory, University of Lampung using Random Design (RBD) consisting of 6 treatments with 3 groups. Treatment A (control), B (300 kg Urea ha-1, 200 kg of SP-36 ha-1, 100 kg of KCl ha-1), C (225 kg Urea ha-1, 150 kg SP-36 ha-1, 75 kg KCl ha-1, 1000 kg Organonitrofos ha-1), D (150 kg Urea ha-1, 100 kg of SP-36 ha-1, 50 kg of KCl ha-1, 1,500 kg Organonitrofos ha-1), E (Urea 75 kg ha-1, SP-36 50 kg ha-1, 25 kg ha-1 KCl, Organonitrofos 2000 kg ha-1), F (3,000 Organonitrofos kg ha-1). The results showed that treatment at a dose of 150 kg of urea ha-1, SP-36 100 kg ha-1, 50 kg ha-1 KCl, Organonitrofos 1500 kg ha-1 is able to increase the growth, production and sweet corn crop nutrient uptake. This treatment was also the most effective treatment of the total biomass of sweet corn plants based on calculations Relative Agronomic Effectivenes (RAE) that is equal to 108.573%. Economical test results showed that treatment at a dose of 300 kg of urea ha-1, SP-36 200 kg ha-1, 100 kg ha-1 KCl most economical compared to other treatments. Keywords: sweet corn, the combination of fertilizer, organonitrofos, nutrient uptake